The application of recurrence plot in tracking characteristics of PU-Based insulation material - İSPİRLİ, MEHMET MURAT (My University, 2022)
Cable joints are the weakest part of underground energy transmission systems due to the presence at the interface between the insulation material and the cable conductor. Underground cables serve under heavy service conditions (dust, dirt, humidity, etc.). So, the tracking resistance of polymers used in joint points of underground cables needs to be determined. In the first section of the study, equivalent samples were prepared under vacuum conditions in laboratory conditions from PU-based filling material used as filler material in low voltage underground cable joints. Prepared samples were tested in an established CTI test setup according to ASTM D5288. Samples were tested in prepared test setup under 600 V, 500 V, 400 V, and 300 V voltages. In the second section of the study, leakage currents were analyzed with the recurrence plot method, which is frequently used in nonlinear times series analysis. Later, recurrence quantification analysis was made by Recurrence Rate (RR) and Determinism (DET) parameters. The behavior of the system occurs less linear with decreased Recurrence Rate in Recurrence Quantification Analysis (RQA). RR and DET parameters increased with the decrease in voltage levels. As a result of, it is revealed that the tracking formation behavior of the PU cable joint becomes more unstable with increasing voltage. Thus, the CTI and RQA are shown to be also available to determine the tracking resistance of cable joints.
Keywords: Temel Bilimler; Natural Sciences; ÇOK DİSİPLİNLİ BİLİMLER; Doğa Bilimleri Genel; Temel Bilimler (SCI); MULTIDISCIPLINARY SCIENCES; NATURAL SCIENCES, GENERAL; Natural Sciences (SCI); Multidisciplinary; Recurrence plot (RP); Recurrence plot quantification (RQA); Tracking failure; Cable joints; Comparative tracking index (CTI); Tracking characteristics; FAILURE